2016
DOI: 10.21475/ajcs.2016.10.06.p7501
|View full text |Cite
|
Sign up to set email alerts
|

Use of physiological parameters to assess seedlings quality of Eugenia dysenterica DC. grown in different substrates

Abstract: The aim of this study was to evaluate the quality and photosynthetic metabolism of Eugenia dysenterica DC. seedlings grown in different substrates. The seed were sown in the following substrates: MecPlant  (MP), rice husks (RH), subsoil (SB), fine vermiculite (FV), coarse sand (CS), tanned cattle manure (CM), decomposed corn silage (CS), and soil collected from around parent plants (SN). The volume-based substrates were formulated as follows:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…The seams results was observed by Mota (2016) which Eugenia Dysentherica seedlings showed increased of root dry weight growth in different substrate. The seedlings of those study showed that the use of organic residues can produce better PSE and ESI, high macronutrients content in the leaves, resulting to more efficient photosynthesis to improve the native plants seedling development (MOTA et al, 2015;MOTA et al, 2016). However, Paiva Sobrinho; (2010) showed that the native species of the Midwest, such as the mangaba (H. speciosa) and baru (Dipteryx alata Vog.)…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The seams results was observed by Mota (2016) which Eugenia Dysentherica seedlings showed increased of root dry weight growth in different substrate. The seedlings of those study showed that the use of organic residues can produce better PSE and ESI, high macronutrients content in the leaves, resulting to more efficient photosynthesis to improve the native plants seedling development (MOTA et al, 2015;MOTA et al, 2016). However, Paiva Sobrinho; (2010) showed that the native species of the Midwest, such as the mangaba (H. speciosa) and baru (Dipteryx alata Vog.)…”
Section: Resultsmentioning
confidence: 95%
“…The R/S values vary according to the species and environmental factors (HODGE, 2004). The seams results was observed by Mota (2016) which Eugenia Dysentherica seedlings showed increased of root dry weight growth in different substrate. The seedlings of those study showed that the use of organic residues can produce better PSE and ESI, high macronutrients content in the leaves, resulting to more efficient photosynthesis to improve the native plants seedling development (MOTA et al, 2015;MOTA et al, 2016).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…They verified that the substrate SB+FC (3: 2) promoted the best nutrition for plants. Mota et al (2016a) concluded that the use of cattle manure mixed with subsoil in 1:3 proportion (v:v), provided the best results for the biometric characteristics and dry matter production of Pouteria gardneriana (Cerrado's native plant, popularly called guapeva).…”
Section: Parameters Of Physiology Nutrition and Quality Of Eugenia Dmentioning
confidence: 99%
“…Dickson et al (1960) created a quality index that considers the ratios mentioned above as well as the accumulation of total DWs. Analyses of physiological parameters (Mota et al, 2016b) and nutritional status (Mota et al, 2016a) has been used to complement the growth and development parameters of native Cerrado seedlings. However, there are few studies that evaluate the production of seedlings based on all these parameters.…”
Section: Parameters Of Physiology Nutrition and Quality Of Eugenia Dmentioning
confidence: 99%